APAKAH PERSEPSI GENDER DAN SIKAP KEWIRAUSAHAAN BERPENGARUH TERHADAP NIAT BERWIRAUSAHA DIGITAL? - Aditya Pratama, Dimas; Ulfa Kamalia, Putri (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to determine the influence of gender perceptions and entrepreneurial attitudes on students' digital entrepreneurial intentions at SMAN 20 Surabaya. The method used in this research is a descriptive method with a quantitative approach, where data is collected to test hypotheses and analyze the relationship between variables numerically using statistical analysis. The sample in this study was 189 grade 10 students at SMAN 20 Surabaya consisting of 10 classes. Each class contains 19 students who are used as samples. The data analysis technique used in this research is the Multiple Linear Regression analysis technique using IBM SPSS Statistics version 25 software. The results of the research show that the variable gender perception has a significant effect on digital entrepreneurial intentions. The entrepreneurial attitude variable has a significant effect on digital entrepreneurial intentions. These two independent variables simultaneously influence digital entrepreneurship intentions.